(3UhQI GdYQH hESQGFjd aj GdcJGH GdeOQSj GddHfGfjs - (3SdGeI, MSjfs ((3HjQhJs (3GdOGQ GdESdGejI ddWHGYIs, 2001)
(3jLeY gPG GdcJGH Hjf WqjGJg OQGSI gj aj CUdgG QSGdI LGeYjI JeJ efGbTJgG NdGd GdYGe (B2000 (3dfjd TgGOI OHdhe GdOQGSGJ GdYdjG aj Yde GdGLJeGY GdJQHhj, MjK cGf GdYed eQJcRkG Ydi JMdjd eVehf GdfUhU GdJYdjejI aj GdcJH GdeOQSjI GddHfGfjI HZjI GSJcTGa hGSJNQGL GdUhQ GdeJfhYI GdJj JMJhjgG(B. (3hgPg GdOQGSI JHMK Yf UhQI GdYQH hESQGFjd hgOagG(B: 1- (3JMOjO GdedGeM GdCSGSjI GdJj JQJSe ef NdGdgG GdUhQI hPdc HJMOjO GdeYWjGJ GdacQjI hGdKbGajI GdJj JJMce aj QSegG(B. 2- (3GSJcTGa GdeHGfj hGdCUhd GdefgLjI GdJj JfWdb efgG GdHQGeL GdJYdjejI hGdfUhU GdeOQSjI aj QSegG dJdc GdUhQI, (B3- (3GdJYqQa Ydi GdGfYcGSGJ GdacQjI hGdKbGajI GdeaJQVI dJdc GdUhQI, (B4- (3JMOjO GdeOi GdPj JYHQ ajg GdcJH GdeOQSjI YfO GdWhGFa Yf CjOjhdhLjGJ gPg GdWhGFa JLGg GdYQH hESQGFjd(B. (3hdCLd HdhZ gPg GdWhGFa CjOjhdhLjGJ gPg GdWhGFa JLGg GdYQH hESQGFjd(B. (3hdCLd HdhZ gPg GdCgOGa GdeMOOI, Jqe HfGA aQVjI GdHMK Ydi GdTcd GdJGdj(B: (3gd GdJeGjR GdYbGFOj hGdCjOjhdhLj Hjf GdaFGJ GddHfGfjI (B((3NUhUkG GdWGFajI efgG(B) (3jJqe EHQGRg OGNd GdeOGQS aj YedjI COdLI GdcJH GdeOQSjI? hgd GdGaJQGb GdacQj Hjf GdTQGFM GdeJYOOI aj GdeLJeY GddHfGfj jfYcS aj GdcJH GdeOQSjI GdeYJeOI aj GdeOGQS GdeJfhYI, ef NdGd fehPL GdYQH hESQGFjd aj Jdc GdcJH? hgd Ef YedjI GdJTQja GdKbGaj aj bVjI HeKd gPg GdCgejI JJe OGNd GdeOGQS hYdi UaMGJ GdcJH abW, Ce Ce eUOQgG ecGf BNQ? Ef GdeVGejf GdJj GMJhGgG GdHMK MGhdJ GdELGHI Yf gPg GdJSGDdGJ hbOeJ eG GSJWGYJ GdJhUd Edjg HNUhUgG, hMGhd GdcTa Yf eOi GdJQGHW GdaYdj Hjf GdJCSjSGJ GdfXQjI GdJj GfWdbJ efgG YedjI QSe GdUhQI, hHjf GdhGbY GdaYdj aj eVGejf GdfUhU GdeHKhKI aj GdcJH GdeOQSjI(B. (3hHTcd YGe jJhRY GdEWGQ GdYGe ddHMK Ydi bSejf CSGSjjf geG GdechfGf dPdc GdEWGQ(B: (3GdfXQj hGdJWHjbj(B: (3JJeMhQ YfGhjf GdbSe GdfXQj Mhd eaghejf CSGSjjf geG ghjI dHfGf(B: (3MjK jJfGhd GdHMK GdETcGdjI GdJGQjNjI GdeJYdbI HGdghjI GdYQHjI ddHfGf hGdbVjI GdadSWjfjI; heSCdI GdhLhO GdESQGFjdj aj adSWjf(B. (3CeG GdbSe GdJWHjbj ajJCda ef KdGKI aUhd, hgh GdbSe GdPj GgJe HGdJfbjH Yf GdUhQI GdJj Jqe JbOjegG Yf GdYQH, hYf GdESQGFjdj aj fUhU GdcJH GdeOQSjI, haj gPG GdbSe CjVkG Jqe GSJNQGL GdeaGgje GdJj bOeJ ef NdGdgG Jdc GdUhQI, hYdjg aEf gPG GdbSe ef GdHMK GgJe HJMdjd eVehf GdcJH GdeOQSjI ef LgI, hHGdeaGgje GdJj MhJgG Jdc GdeVGejf ef LgI KGfjI(B.s
(3GdfhY (B: (3cJGHs
Keywords: Israel; Israel; Livres Scolaires; Textbooks; (3GSQGFjds; (3GdcJGH GdeOQSjs